APPLICATION OF MICROSURGICAL TECHNOLOGIES IN SURGERY OF SMALL AND MIDDLE INTESTINE IN CONDITIONS OF EXPERIMENTAL INTESTINAL OBSTRUCTION AND GENERAL PERITONITIS - V. K. Esipov; I. I. Kagan; A. V. Donskov; A. R. Kurmashev; S. V. Yashnikov (Креативная хирургия и онкология)
The article contains data of morphological analysis of wound healing and anastomosis of small and middle intestine, formed with appliance of microsurgical operative procedures, taking into consideration the stages of pathological process and type of microsurgical sutures. The article shows the meaning of peculiarities of microanatomy of the wall in small and middle intestine in case of obstruction and peritonitis, at implementation of microsurgical administration of operation. It also shows possibility and effectiveness of implementation of microsurgical technology while wound closure of small and middle intestine in peritonitis and application of colonic anastomosis at intestinal obstruction. Possibility of wound and anastomosis healing is proved.